Evaluation of antioxidant activity and identification of bioactive compounds of Senna siamea (Lam.) leaf extract using solvent and ultrasound-assisted extractions - Phaiphan, Anuthida (2016)
This research was conducted to evaluate antioxidant activity and identification of bioactive compounds of S. siamea leaf extracted using solvent and ultrasound-assisted extractions (UAE). A randomized complete block design with three replicates and central composite design (CCD) as a response surface methodology (RSM) were used to design and optimize the experiments. Effects of different solvents and locations on the bioactive compounds and antioxidant activities of S. siamea leaf were investigated. The results showed that the various solvent extractions had different amount of antioxidant compounds and activities. Methanol extract presented the highest efficiency values of yield, TPC, tannin content, DPPH, FRAP, and TEAC values, followed by extracts of water, ethanol, and ethyl acetate, respectively. Water extracts had the highest concentration of ascorbic acid, varying from 6.59-9.43 mg/g dw. Meanwhile, Beta-carotene content of ethyl acetate extracts was the highest (28.20 mg/g dw) with significant (p<0.05) differences among locations. The correlation coefficients of antioxidant compounds with three of the antioxidant activity assays (%DPPH, FRAP, and TEAC) revealed that TPC, tannin content, and ascorbic acid of the extracts correlated strongly with antioxidant activities. The average of R2 of TPC, tannin content, and ascorbic acid was 0.976, 0.955, and 0.833, respectively. The optimization of solvent extraction and UAE of antioxidant compounds and antioxidant activities from S. siamea leaf was investigated. RSM and CCD were used to design and optimize experimental conditions. The result showed that the optimum conditions for solvent extraction were 49% of ethanol concentration, temperature at 51oC, and 22.5 min extraction time. Ethanol concentration, temperature, and time were the most important variables that had effect on the responses. For UAE, the optimum conditions were 40%ethanol concentration, temperature at 37oC, and time of 7 min. Ethanol concentration was the most important variable that had an effect on the responses, followed by time and temperature. The UAE extracts exhibited higher efficiency, yield, TPC, %DPPH, and FRAP values than solvent extracts. The yield, TPC, %DPPH, and FRAP values increased 10.6%, 20.7%, 9.4%, and 29.6%, respectively from the solvent extraction. These results from the RSM clearly revealed that UAE has potential and is efficient to be used to extract TPC and antioxidant activities in higher yields compared with solvent extractions. However, more identification studies are required to identify the bioactive compounds in the most desirable extract from S. siamea leaf. The individual phenolic acids and flavonoids were carried out using high performance liquid chromatography. The results showed that bioactive compounds in soluble extracts are significantly (p<0.05) higher than cell wall-bound extracts. It was further revealed that soluble phenolic acids are the major phenolic acids in the leaf. Caffeic acid was found as the most abundant phenolic acid in the leaf extracts, followed by gallic acid, and protocatechuic acid at 42.12, 25.27, and 21.65 mg/g dw, respectively, mainly in its soluble form. On the other hand, protocatechuic acid was the main phenolic acid found in cell wall-bound extracts at 19.13 mg/g dw. The flavonoid contents were in the range of 0.38-137.14 mg/g dw in the extracts. Epicatechin and catechin contents were the main flavonoids present in soluble extracts, which were 137.14 and 27.02 mg/g dw and also were the only flavonoids detected in cell wall-bound extracts, which were 10.19 and 16 mg/g dw, respectively. The results exhibited that the main portions of bioactive compounds in the leaf were present in soluble extracts. It indicated that S. siamea leaf may be regarded as a valuable source of antioxidant-rich nutraceuticals. The potential applications of S. siamea leaf antioxidants could be a value-added to the cosmetic or processed foods industries.